2015
DOI: 10.1038/mi.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

The short form of TSLP is constitutively translated in human keratinocytes and has characteristics of an antimicrobial peptide

Abstract: Thymic stromal lymphopoietin (TSLP) has multifaceted immunological functions ranging from maintenance of tolerance to induction of disease. Two human transcript variants of TSLP are described: a long form (variant 1; lfTSLP) consisting of four exons and an alternative, short form (variant 2; sfTSLP) that lacks two exons compared with variant 1. SfTSLP has not been described at the protein level or functionally studied. Here, we demonstrate that the human sfTSLP is the predominant form of TSLP, constitutively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
99
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 27 publications
5
99
2
3
Order By: Relevance
“…Although TSLP mRNA expression has already been detected in healthy skin, its protein expression (Bjerkan et al, 2015;Fornasa et al, 2015) was found only in inflamed epidermis (AD, psoriasis) until now (Soumelis et al, 2002;Ziegler, 2012). The conflicting data between the previous publications and our current study might be explained by that the other investigators most probably used healthy SGP skin and no SGR samples as controls of AD or psoriasis.…”
Section: Discussioncontrasting
confidence: 54%
“…Although TSLP mRNA expression has already been detected in healthy skin, its protein expression (Bjerkan et al, 2015;Fornasa et al, 2015) was found only in inflamed epidermis (AD, psoriasis) until now (Soumelis et al, 2002;Ziegler, 2012). The conflicting data between the previous publications and our current study might be explained by that the other investigators most probably used healthy SGP skin and no SGR samples as controls of AD or psoriasis.…”
Section: Discussioncontrasting
confidence: 54%
“…Hence, upregulation of sfTSLP may be one of the mechanisms of vitamin D-mediated protection against airway inflammation, supporting its advantages in the treatment of asthma3435. sfTSLP has been confirmed to exert potent antimicrobial activity22 and have anti-inflammatory activities in inflammatory disorders of the bowel19. At the protein level, sfTSLP encompasses the last 63 residues of lfTSLP.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in primary human keratinocytes, toll-like receptor ligands, a pro-inflammatory cytokine (TNF-α), and Th2 cytokines (IL-4 and IL-13) predominantly upregulate gene expression of lfTSLP, but not sfTSLP21. Another study found that synthetic sfTSLP exerts potent antimicrobial activity and that sfTSLP is the predominant form of TSLP, being the form widely and constitutively expressed in keratinocytes and saliva at steady state, both at the mRNA and protein levels22. In inflammatory disorders of the bowel, lfTSLP was shown to promote inflammation and is only expressed during inflammation, while sfTSLP is expressed under steady-state conditions and inhibits inflammation19.…”
mentioning
confidence: 99%
“…Among these, a growing number of AMPs has been identified and the corresponding antimicrobial activity discerned [4][5][6][7]. For instance, the salivary short form of Thymic stromal lymphopoietin (isoform 2) results from proteolytic cleavage of Thymic stromal lymphopoietin and displays antimicrobial properties [4,8]. Similarly, eotaxin-3/CCL26 is generated by mast cell protease-mediated cleavage during allergic inflammatory responses to bacterial infections of the airways and is active against several airway pathogens, including Streptococcus pneumoniae and Staphyloccous aureus [5].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, 2 thousands of fragmentation peptides can be found in the extracellular milieu [1][2][3]. Among these, a growing number of AMPs has been identified and the corresponding antimicrobial activity discerned [4][5][6][7]. For instance, the salivary short form of Thymic stromal lymphopoietin (isoform 2) results from proteolytic cleavage of Thymic stromal lymphopoietin and displays antimicrobial properties [4,8].…”
Section: Introductionmentioning
confidence: 99%